Bioavailability‐based chronic toxicity measurements of permethrin to Chironomus dilutus. (16th April 2013) - Du, Juan; Pang, Junxiao; You, Jing
ABSTRACT: Compared with acute toxicity, chronic exposures to low levels of contaminants are more environmentally relevant, but fewer data are available. In the present study, sediment toxicity of the pyrethoid permethrin to Chironomus dilutus was determined. The whole‐life‐cycle toxicity testing was conducted with the endpoints covering survival, growth, emergence, and reproduction. Permethrin caused 50% lethality in C. dilutus at 1.83 ± 1.13 µg/g organic carbon (OC) and 1.20 ± 0.55 µg/g OC after exposures of 20 d (before pupation) and 58 d (the end of the testing), respectively. The 5% and median effect concentrations (EC5 and EC50) represented the marginal and toxic levels of the sublethal effects, respectively, and effect data were all normalized to the controls before Probit analysis. The EC5s for growth, emergence, and reproduction were 0.034 ± 0.006 µg/g OC, 0.016 ± 0.008 µg/g OC, and 0.009 ± 0.008 µg/g OC, respectively; the respective EC50s were 1.09 ± 0.56 µg/g OC, 0.838 ± 0.077 µg/g OC, and 0.039 ± 0.105 µg/g OC. In addition, a 24‐h Tenax extraction was employed to better assess permethrin bioavailability. Ultimately, response spectra with a series of endpoints were developed for permethrin using either OC‐normalized bulk sediment concentrations or bioavailability‐based Tenax extractable concentrations as the dose metric. The development of bioavailability‐based chronic toxicity endpoints for sediment‐associated permethrin would provide valuable benchmarks for evaluating ecological risk of this contaminant and contributing to improve sediment management policies. Environ Toxicol Chem 2013;32:1403–1411. © 2013 SETAC